AN AUTHENTICITY ANALYSIS OF CONVERSATIONAL TEXTS IN THE INDONESIAN EFL TEXTBOOKS - Setiaji, Sholeh (2016)
Although the exposure of naturally occurring language use is important for learners (Carter et al., 2011; Tomlinson, 2011), in the Indonesian context artificiality can still be found in some teaching and learning materials published and used in the EFL classroom. Regarding this issue, this thesis reports on the analysis of the authenticity of three Indonesian published textbook materials (Pathway to English 1, 2, and 3) which are commonly used in EFL practices. Ten dialogues from the textbook materials with ten different topics were selected as the textbook data (TD). To find out how they display the features of authentic language use, they were compared with their reality-like equivalents or reality-like data (RD) which were performed in natural contexts by six native speakers acting as the reality-like dialogue performers. Both sets of data were transcribed and contrasted across a range of discourse features: hesitation markers, turn-taking, back-channels and lexical density (Gilmore, 2004). The findings suggest that, in terms of hesitations, latches, and overlaps, the textbook dialogues differ significantly from their reality-like equivalents indicated by the absence of the features in TD and the consistent inclusion in RD. Therefore, it can be concluded that textbook audio dialogues do not reflect the ways in which natural conversations are produced in the real contexts. Such a clear gap may be due to some pedagogical justifications such as emphasis on particular learning objectives, teachability, learnability, and presentation of the scripts in the textbooks. Based on the research findings, it is recommended that textbook writers start incorporating natural dialogue features into students' textbooks. Moreover, since both students and teachers need more exposure to the authentic use of the target language, their teaching and learning process should provide activities which represent how native speakers interact. As a final point, the future research needs to focus on wider aspects of a natural interaction such as suprasegmental features, the grammatical points and the pragmatic features.; Meskipun pemajangan terhadap penggunaan bahasa yang natural sangat penting bagi siswa (Carter dkk., 2011; Tomlinson, 2011), di Indonesia masih banyak ditemukan ketidakotentikan pada buku-buku teks yang digunakan dalam pembelajaran Bahasa Inggris. Berkaitan dengan hal tersebut, penelitian ini bertujuan untuk mengetahui keotentikan tiga buku teks terbitan penerbit Indonesia (Pathway to English 1, 2, and 3) yang umum digunakan dalam pembelajaran Bahasa Inggris. Studi komparatif digunakan dalam penelitian ini untuk mengidentifikasi bagaimana dialog-dialog dalam buku teks memasukan fitur-fitur bahasa yang otentik yaitu hesitation markers, turn-taking, back-channels dan lexical density (Gilmore, 2004). Sepuluh dialog dengan topic yang berbeda dipilih dari buku-buku sampel secara purposive sebagai textbook data (TD). Sedangkan data pembanding atau reality-like data (RD) dikumpulkan dengan cara meminta enam orang penutur bahasa Inggris asli, yang juga dipilih secara purposive, untuk melakukan dialog yang ekuifalen dengan dialog pada TD. Kedua jenis data ditranskrip dan dibandingkan berdasarkan jumlah kemunculan fitur-fitur bahasa natural. Hasil temuan menunjukan, dalam hal hesitations, latches, dan overlaps, dialog pada buku teks berbeda secara signifikan dengan dialog natural, yang diindikasikan dengan absennya fitur-fitur tersebut pada TD dan kemunculan yang konsisten pada RD. Dari hasil tersebut dapat disimpulkan bahwa audio dialog pada buku teks tidak merefleksikan bagaimana bahasa Inggris digunakan di dalam konteks yang sebenarnya. Perbedaan tersebut mungkin disebabkan karena penulis bermaksud untuk mengakomodasi aspek pedagogi seperti tujuan pembelaran, tingkat teachability dan learnability, serta presentasi naskah dialog dalam buku teks. Berdasarkan temuan tersebut, penulis buku teks sebaiknya memulai untuk menyertakan fitur-fitur dialog natural di dalam buku-buku teks. Selain itu, mengingat baik guru maupun siswa sangat memerlukan pemajangan terhadap penggunaan bahasa target yang otentik, di dalam proses pembelajaran aktifitas-aktifitas yang dilakukan sebaiknya merepresentasikan bagaimana penutur asli berinteraksi menggunakan bahasa target. Terahir, penelitian selanjutnya diharapkan difokuskan pada aspek lain yang lebih luas sperti fitur suprasegmental, gramatikal, dan pragmatic.